Adsorbed Water on Nano-Silicon Powder and Its Effects on Charge and Discharge Characteristics as Anode in Lithium-Ion Batteries. Issue 1 (1st January 2017) - Yoshida, Shuhei; Masuo, Yuta; Shibata, Daisuke; Haruta, Masakazu; Doi, Takayuki; Inaba, Minoru
Abstract : The amounts of adsorbed water on several kinds of carbon and silicon materials including Si nano-flake powder (Si LeafPowder, Si-LP) were determined at 250°C. It was found that nano-sized Si materials adsorb a large amount of water even after being dried at 120°C because of the hydrophilicity of the surface and the high specific surface area. The adsorbed water on Si-LP can be removed, but not completely, after drying at a 180°C. The charge and discharge characteristics of Si-LP, especially the initial irreversible capacity and the coulombic efficiencies upon repeated cycling, were significantly improved by removal of the adsorbed water at 180°C. The 180°C-dried sample also suppressed gas evolution during the initial charging and discharging cycle. From the results of gas analysis, it was found that gases evolved from the Si-LP electrodes were mainly H2 and CO2 . From the results of charge and discharge tests and gas analysis, the effect of the adsorbed water on the irreversible decomposition of the electrolyte solution was discussed.